Tubal recanalisation-microsurgical tubal reversal anastomosis - Rajendran, M. K. (International Surgery Journal, 2018)
Background: Nowadays, in India, to control population, we are strictly following permanent methods of sterilization after one or two children. Because of some unfortunate things like RTA or some natural calamities, some parents have lost one or both the children in that situation. To study the outcome of the procedure patency of the tube, complications, pregnancy if happens during the study period. Methods: Totally 65 female patients were included in the study. Authors have the patients for past 18 years including post tubectomy patients with is variable age and duration after sterilization and all methods of sterilization except fimbriectomy. For all cases, we have done all basic investigation, USG, and HSG. Results: Totally 65 patients are followed regularly from 2008. The success rate (pregnancy rate) is >90%. In these patients, pregnancy outcome was in form of intrauterine pregnancy (90%) ectopic pregnancy (2%), term viable pregnancy (3%) and spontaneous abortion (less than 1%). Conclusions: In the past, in most of the studies, the success rate (pregnancy rate) is more in the age group of <30 years. But in present study even in >30 years age and any long duration of the post-sterilization period, the success rate is more, because the two-layer technique 8-0 prolene under loupe magnification is the leading factor for the success rate (pregnancy rate).